Power up 2 : pupil's book - Nixon, Caroline (London : Macmillan Education, 2018)
Power Up provides the perfect start to life's great adventure, creating confident learners who embrace life. Meet vibrant characters who students will love. Foster collaboration through real-world missions, deepen learners' social and cognitive skills and explore embedded exam preparation ensuring everyone reaches their full potential.
Keywords: English language -- Juvenile literature. -- Problems, exercises, etc; English language -- Study and teaching (Elementary)